Applying system dynamics modelling to modal shift: A systematic review - Zeynab Pirouzrahi; Thierry Vanelslander; Ali Nassiri Aghdam (Sustainable Futures)
The shift of freight transportation to more sustainable modes is a pressing issue in many countries. Effective policymaking to reach this dynamic goal needs the scientific support of models to assess alternative policies. In this way, the system dynamics approach can model the freight transport sector as a dynamic and complex system in which one strategy may impact multiple factors. Also, time lags are important parameters in analyzing policies. Due to the importance and benefits of using system dynamics in solving policy issues in complex transportation systems, we can see a lot of studies that have used this model from different perspectives, including modal shift and sustainability. However, finding a broad model in system dynamics that includes modal distribution, whether as a policy instrument or effecting sub-system, remains a challenge. This work aims to bridge that knowledge gap. We carried out a systematic literature review in the field of freight transportation, with a focus on modal shift and mode share. After applying identification and screening criteria to all relevant records, we included 24 studies in our analysis. We outline the core causal loops of the key modules identified to provide an initial framework for future quantitative research. In the majority of the studies reviewed, these modules were either not addressed at all or were addressed only partially. This framework can be translated into an empirical model in future research to guide policymakers in developing effective strategies to promote sustainable freight transportation by leveraging the insights gained from system dynamics modeling.